Expert Answers

An illustration of the letter 'A' in a speech bubbles

We have to find x given that 8^(4x-6)-1/64=0

8^(4x-6) - 1/64 = 0

=> 8^(4x-6) = 1/64

=> 8^(4x-6) = 8^-2

as the base is the same on both the sides we can equate the exponent.

=> 4x - 6 = -2

=> 4x = -2 + 6

=> 4x = 4

=> x  = 4/4

=> x = 1

Therefore x is equal to 1.

Approved by eNotes Editorial Team

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial